ON THE QUESTION OF AESTHETIC EDUCATION OF FUTURE PHYSICAL EDUCATION TEACHERS (Web of Teachers: Inderscience Research, 2026)
The article interprets the level, content and criteria of a physical education teacher's preparation for independent knowledge in his profession. The conditions for the formation of this preparation in the process of training personnel in physical education are revealed.